Without Peace there is No End to Hunger: The contribution of the Two Degree Initiative (2DI) to Peace and Security - Bonilla Findji, Osana; Schapendonk, Frans; Läderach, Peter R.D. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
This document and analysis highlight the importance of Climate Security for the Two Degree Initiative (2DI) and its articulation in the 2DI impact pathway and the Global Themes. This is an invitation to include Climate Security in the framing of 2DI recognizing that: